Ultrahigh-strength steel belt and manufacturing method thereof

By controlling chemical composition and process, a uniform granular bainite structure is formed, which solves the problem that ultra-high strength steel is difficult to achieve low anisotropy and high mechanical uniformity under tensile strength of 1000MPa, and achieves high strength and high uniformity Ultra-high strength steel belt, suitable for high-precision automotive parts.

CN119162503AActive Publication Date: 2024-12-20BAOSHAN IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310734190.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

When existing ultra-high strength steels reach tensile strength of 1000MPa, it is difficult to achieve low anisotropy and high mechanical uniformity of the same coil, resulting in uneven performance in automotive parts and difficult to meet the requirements of bidirectional or multidirectional mechanical properties.

Method used

By controlling the content of chemical components such as C, Si, Mn, B, Al, Cr, Mo, Ti, V, and Nb, a uniformly dispersed granular bainite microstructure is formed in the shape of a coral sea, and a multi-stage cooling and annealing process is used. , ensure uniformity of the steel belt in length, width and thickness directions.

Benefits of technology

It achieves an ultra-high strength steel belt with tensile strength of 1000MPa, with low anisotropy and high mechanical uniformity of the same coil, and improves forming performance and performance uniformity, and is suitable for high precision and high stability automotive parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162503A_ABST
    Figure CN119162503A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh-strength steel strip, which contains Fe and inevitable impurity elements, and further contains the following chemical elements in percentage by mass: 0.13-0.20% of C, 0.20-0.30% of Cr, 0.20-0.30% of Mo, 0.20-0.30% of Mo and the balance of Fe. 0.15% to 0.50% of Si; 1.4 to 2.0 percent of Mn; b: 0.001 to 0.004 percent of the total weight of the raw materials; 0.01 to 0.04 percent of Al; cr: 0.1 to 0.4%; mo: 0.1 to 0.4%; ti + V + Nb is less than or equal to 0.02%; the microstructure of the steel comprises granular bainite which is uniformly dispersed in a coral sea shape. Correspondingly, the invention further discloses a manufacturing method of the ultrahigh-strength steel belt. The tensile strength of the ultra-high-strength steel belt reaches 1000 MPa, and meanwhile the ultra-high-strength steel belt has low anisotropy and high same-roll mechanical uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength steel and a manufacturing method thereof, and in particular to an ultra-high-strength steel with a coating and a manufacturing method thereof. Background Art

[0002] With the development of the automobile industry, the design of automotive parts is becoming more and more compact, light, thin, and high-precision, and the mechanical properties in two or even multiple directions are required to be as uniform as possible to ensure high-beat production, high-precision assembly, and high-stability service of parts. This requires not only that the material has ultra-high strength and good forming performance, but also low anisotropy or high isotropy in mechanical properties, and extremely high performance uniformity.

[0003] At present, ultra-high-strength steel is increasingly widely used in automotive parts. At the same time, since ultra-high-strength steel is currently produced in an integrated manner on a large scale, this places extremely high demands on the mechanical uniformity of the ultra-high-strength steel in the same roll.

[0004] However, in the prior art, as the strength of high-strength steel increases to 1000MPa, it is extremely difficult to obtain steel strips with low anisotropy and high mechanical uniformity in the same roll. Taking the data in the published Journal of Plastic Engineering, 2021, 28(7):124-130 as an example, the strength difference between the transverse and longitudinal directions of dual-phase steel with a tensile strength of 800MPa is about 8MPa, but when the tensile strength of dual-phase steel reaches 1000MPa, the strength difference between the transverse and longitudinal directions can be as high as about 40MPa.

[0005] In addition, the Chinese patent document with publication number CN104018092A, publication date March 8, 2017, and titled “A 750MPa-level high-strength and high-mechanical-property uniformity steel plate and its manufacturing method”, discloses that the tensile strength of the steel is only at the 800MPa level, and the mechanical uniformity in the transverse, longitudinal and 45° directions can only reach <20MPa.

[0006] For example, the Chinese patent document with publication number CN102397891A, publication date March 23, 2018, and titled “A method for improving the uniformity of steel strip performance”, although it can make the strength uniformity of the steel strip in the width direction higher and the strength fluctuation is only 5 to 15 MPa, the tensile strength of this type of steel is only about 350 MPa to 600 MPa.

[0007] From this, it can be seen that it is technically difficult to obtain ultra-high-strength steel with low anisotropy (or high isotropy) and high mechanical uniformity in the same roll, while achieving a strength of 1000MPa. Summary of the invention

[0008] One of the objects of the present invention is to provide an ultra-high strength steel strip having low anisotropy and high mechanical uniformity in the same coil while achieving a tensile strength of 1000 MPa.

[0009] In order to achieve the above object, the present invention provides an ultra-high strength steel strip, which contains Fe and inevitable impurity elements, and further contains the following chemical elements in the following mass percentages:

[0010] C: 0.13~0.20%; Si: 0.15~0.50%; Mn: 1.4~1.9%; B: 0.001~0.004%; Al: 0.01~0.04%; Cr: 0.1~0.4%; Mo: 0.1~0.4%; Ti+V+Nb≤0.02%;

[0011] Its microstructure consists of uniformly dispersed granular bainite in the shape of a coral sea.

[0012] Accordingly, the present invention also provides an ultra-high strength steel strip, the mass percentage of each chemical element of which is:

[0013] C: 0.13~0.20%; Si: 0.15~0.50%; Mn: 1.4~2.0%; B: 0.001~0.004%; Al: 0.01~0.04%; Cr: 0.1~0.4%; Mo: 0.1~0.4%; Ti+V+Nb≤0.02%; the balance is Fe and unavoidable impurity elements.

[0014] Furthermore, in the ultra-high strength steel strip of the present invention, the mass percentage of each chemical element satisfies at least one of the following items:

[0015] C: 0.14~0.18%;

[0016] Ti+V+Nb≤0.02%.

[0017] In the ultra-high strength steel strip of the present invention, the design principles of each chemical element are as follows:

[0018] C: In the ultra-high strength steel strip described in the present invention, the C element not only controls the microstructure phase change, but also forms alloy carbides with other alloy elements, thereby affecting the strength, formability and performance uniformity of the steel plate. In the present invention, when the C element content in the steel is lower than 0.13%, on the one hand, the strength of the steel will not meet the target requirements, and on the other hand, it will also lead to insufficient formation of granular bainite; and if the C element content in the steel is higher than 0.20%, it is easy to generate martensitic structure, coarse cementite, and other forms of bainite (non-granular bainite, such as upper bainite), thereby deteriorating the performance and performance uniformity of the steel strip. Based on this, the present invention controls the mass percentage of C between 0.13 and 0.20%.

[0019] Si: In the ultra-high-strength steel strip described in the present invention, Si is a necessary element for steelmaking deoxidation. It has a certain solid solution strengthening effect and also has a certain influence on the formation of polygonal ferrite and bainite. In the present invention, when the Si content in the steel is lower than 0.15%, it is difficult to obtain a sufficient deoxidation effect; and when the Si content in the steel is higher than 0.5%, on the one hand, it is easy to form iron oxide scale or tiger stripe color difference, which is not conducive to the surface quality of the steel plate, and on the other hand, it will affect the formation of granular bainite, and cause polygonal ferrite and carbon-free bainite to be easily formed in the steel, affecting the performance uniformity. Based on this, the present invention controls the mass percentage of Si between 0.15 and 0.5%.

[0020] Mn: In the ultra-high strength steel strip described in the present invention, Mn is one of the key controlling elements for the phase transformation of the steel structure. When the Mn element is too low, on the one hand, the strength of the steel will not meet the target requirements, and on the other hand, it will also lead to insufficient formation of granular bainite; and when the Mn content is too high, it will not only deteriorate the corrosion resistance and welding performance, promote the formation of non-granular bainite structures such as martensite, but also intensify the tendency of grain coarsening and the formation of banded structures or center segregation, reduce the formability of the steel, and degrade the uniformity and performance uniformity of the steel strip. Based on this, the present invention controls the mass percentage of Mn between 1.4 and 2.0%.

[0021] B: In the ultra-high strength steel strip described in the present invention, the B element is not only conducive to the formation of bainite in the steel, but also has a great influence on the strength and hardness of the steel plate. If the B element content in the steel is less than 0.001%, the strength of the steel will not meet the target requirements; and when the B element content in the steel is higher than 0.004%, brittle borides are easily generated, affecting the formability and uniformity of the steel plate. Based on this, the present invention controls the mass percentage of B to between 0.001 and 0.004%.

[0022] Al: In the ultra-high strength steel strip described in the present invention, Al is added to the steel only as a deoxidizing element, which can remove the O element in the steel to ensure the performance and quality of the steel. Therefore, the present invention controls the mass percentage of Al to be between 0.01 and 0.04%. Although in some prior arts, Al is added to the steel in large quantities (≥0.1%) as a ferrite forming element and an element that inhibits the precipitation of carbides, in the hope of bringing about solid solution strengthening, or by changing the phase transformation temperature (such as A1, A3), bainite formation kinetics and carbide precipitation kinetics through the addition of Al to change the phase transformation of the steel, forming residual austenite or carbon-free bainite, and ultimately improving the strength of the steel, it is not beneficial to improve the performance uniformity and isotropy of the steel strip, so there is no need to add a large amount of Al to avoid causing a substantial increase in cost and difficulty in steelmaking.

[0023] Cr and Mo: In the ultra-high strength steel strip described in the present invention, Cr and Mo can increase the hardenability of the steel strip, increase the incubation period of pearlite and ferrite, inhibit the formation of pearlite and ferrite, and make it easy to obtain bainite structure during cooling. Therefore, when the Cr and Mo content is too low, insufficient granular bainite formation will result, while when the Cr and Mo content is too high, on the one hand, more martensite, tempered martensite and other structures are easily formed, deteriorating the forming performance of the steel strip, and on the other hand, it is easy to form a banded structure morphology or center segregation in the steel strip, thereby deteriorating the uniformity of the steel strip. Therefore, in the present invention, Cr is controlled to be 0.1-0.5%, and Mo is controlled to be 0.1-0.5%.

[0024] Ti, Nb and V: In the ultra-high strength steel strip described in the present invention, Ti, Nb and V are not intentionally added as common micro-alloying elements that are beneficial to the performance of steel, but are controlled as residual elements in steelmaking. Since these micro-alloying elements will form carbonitride precipitation from the formation of slabs during steelmaking continuous casting, especially the precipitation of larger carbonitrides such as TiN, and throughout the entire production process of the steel strip, it is extremely difficult to control the uniform, stable and on-demand precipitation of these carbonitrides, which will have an adverse effect on the uniformity of the performance of the steel strip. Therefore, in the present invention, Ti+Nb+V is limited to ≤0.02%, and it is further preferably limited to Ti+Nb+V≤0.01%.

[0025] Furthermore, in the ultra-high strength steel strip described in the present invention, the mass percentage of each chemical element also satisfies: 2.7≤(Cr+Mo) / C≤3.3, where each chemical element in the formula is substituted with the value before the percentage sign of its mass percentage.

[0026] In the present invention, since C, Cr, and Mo play a key role in the phase transformation of bainite, it is further preferably controlled to be 2.7≤(Cr+Mo) / C≤3.3. If (Cr+Mo) / C is too low, it is easy to cause the bainite phase area to be too small, the hardenability of the steel strip is insufficient, and during annealing production, too much ferrite, pearlite, upper bainite and other structures will be generated due to insufficient cooling rate. If (Cr+Mo) / C is too high, the hardenability of the steel strip will be too high and the martensite transformation point temperature will be high, resulting in excessive martensite in the steel strip.

[0027] Furthermore, in the ultra-high strength steel strip of the present invention, the mass percentage of the inevitable impurity elements satisfies at least one of the following conditions: P≤0.012%, S≤0.003%, and N≤0.004%.

[0028] The impurity elements in the present invention are only P, S and N. If the technical conditions permit, it is hoped that the content is as low as possible. Furthermore, the content can be controlled to be P≤0.012%, S≤0.003%, and N≤0.004%.

[0029] Furthermore, in the ultra-high strength steel strip of the present invention, the volume phase ratio of the granular bainite is ≥95%.

[0030] Furthermore, in the ultra-high strength steel strip of the present invention, the area of ​​the granular bainite is ≤5 μm 2 , aspect ratio ≤2:1.

[0031] Furthermore, in the ultra-high strength steel strip of the present invention, any cross-sectional area of ​​50 μm or less in all regions outside the upper and lower surfaces of the steel strip in the thickness direction is 30 μm or less. 2 The granular bainite is distributed in the region of 0.1 μm.

[0032] Furthermore, in the ultra-high strength steel strip of the present invention, any cross-sectional area of ​​10 2 Granular bainite is distributed in the area of ​​μm.

[0033] This indicates that granular bainite is basically distributed in the middle region 30 μm away from the surface of the steel strip.

[0034] Furthermore, in the ultra-high strength steel strip of the present invention, its microstructure also includes ferrite, and the volume phase ratio of the ferrite is 0.1-4.5%.

[0035] In addition to granular bainite and ferrite, the microstructure of the ultra-high strength steel strip of the present invention may also contain retained austenite, other forms of bainite, tempered martensite, titanium carbonitride (or niobium, or vanadium) and martensite. However, the content of such structures is relatively small, the sum of the volume phase ratios does not exceed 0.5%, and the amount of the phase ratios satisfies the following: retained austenite>other forms of bainite>tempered martensite>titanium carbonitride (or niobium, or vanadium)>martensite.

[0036] Furthermore, the ultra-high strength steel strip described in the present invention has a tensile strength ≥1000MPa and a yield strength ≥780MPa; and the low anisotropy satisfies: the difference in yield strength between the transverse and longitudinal directions at the same position on the steel strip is ≤25MPa, and the difference in tensile strength is ≤20MPa; the mechanical uniformity of the same coil satisfies: for the same steel coil, along its length or width direction, the difference in yield strength at different positions in the same tensile direction is ≤25MPa, and the difference in tensile strength is ≤20MPa.

[0037] Furthermore, the ultra-high strength steel strip described in the present invention has a tensile strength ≥1000MPa and a yield strength ≥780MPa; and the low anisotropy satisfies: the difference in yield strength between the transverse and longitudinal directions at the same position on the steel strip is ≤20MPa, and the difference in tensile strength is ≤15MPa; the mechanical uniformity of the same coil satisfies: for the same steel coil, along its length or width direction, the difference in yield strength at different positions in the same tensile direction is ≤20MPa, and the difference in tensile strength is ≤15MPa.

[0038] Furthermore, the ultra-high strength steel strip of the present invention has an elongation at break ≥ 10%, and / or a hole expansion ratio ≥ 50%.

[0039] Another object of the present invention is to provide a method for manufacturing an ultra-high strength steel strip, by which a steel strip having a tensile strength of 1000 MPa and low anisotropy and high mechanical uniformity in the same roll can be produced.

[0040] Based on the above purpose, the present invention also provides a method for manufacturing an ultra-high strength steel strip, which comprises the steps of:

[0041] smelting and casting;

[0042] Hot rolling;

[0043] Post-rolling cooling and coiling: Post-rolling cooling adopts fast cooling and slow cooling alternately for multi-stage cooling. Finally, for the area outside 100m of the head and tail of the steel strip, the main body of the steel strip is cooled to the main coiling temperature of 440℃~520℃ at a cooling rate of 5~100℃ for coiling. For the area within 100m of the head and tail of the steel strip, the head and tail of the steel strip are cooled to the head and tail coiling temperature of 480℃~560℃ at a cooling rate of 5~25℃ for coiling.

[0044] Pickling and cold rolling;

[0045] Annealing: heat to 840-900°C at a heating rate of ≤50°C / s and keep warm; then cool to 700-780°C at a cooling rate of 2-20°C / s and keep warm; then cool to 360-430°C at a cooling rate of 20-50°C and keep warm; then heat to 440-480°C at a heating rate of 5-30°C / s; then cool to 330-400°C at a cooling rate of 0.1-0.5°C / s; finally cool to room temperature at a cooling rate of 15-50°C / s and coil.

[0046] The present invention adopts the above-mentioned post-rolling cooling and coiling process in order to obtain a uniform cross-sectional shape of the steel strip, a good plate shape and a uniform precursor structure, so as to ensure that in the annealing stage the steel strip can obtain a coral sea-like uniformly dispersed granular bainite in the length, width and thickness directions, so as to ensure that the final steel strip can obtain low anisotropy and high coiling performance uniformity.

[0047] The main purpose of adopting a multi-stage cooling scheme is to ensure that the hot coil has uniform structure after coiling. In the post-rolling cooling stage, the input of cooling water will cause extremely efficient heat exchange and extremely rapid temperature changes, which can easily cause uneven structure performance in local areas of the hot coil. In addition, due to the fluctuations in the cross-sectional shape and plate shape of the steel strip after fine rolling, it is also easy to cause water accumulation in local areas of the hot coil, resulting in abnormal structure performance in local areas. Therefore, the main idea of ​​the multi-stage cooling scheme of the present invention is to adopt a step-by-step fast and slow cooling alternating method to reduce the impact of cooling water input on the structure performance of the hot coil, gradually reduce the cooling rate, and must be followed by slow cooling after fast cooling to eliminate the influence of heat exchange fluctuations and water accumulation of cooling water.

[0048] In terms of the final coiling temperature, the present invention adopts the method of low-temperature coiling of the main body of the steel strip and increasing the coiling temperature within 100m from the head to the tail, mainly considering the influence of environmental heat exchange after coiling on the performance of the hot coil structure, and forming bainite structure in a relatively stable temperature range as much as possible: first, the coiling temperature of the main body as low as possible greatly reduces the influence of environmental heat exchange on the dynamics of hot coil structure formation; secondly, the coiling temperature is slightly increased at ≤100m from the head to the tail, which is also considered that the environmental heat exchange at the head and tail of the hot coil is high, which is easy to produce a large temperature drop. Thirdly, 440℃~520℃ is the main temperature range for bainite formation. If the temperature is too low, martensite structure is easy to form, and if the temperature is too high, it is easy to produce uneven heat exchange with the environment, thereby forming an uneven structure (pearlite, bainite or martensite may be formed in different areas).

[0049] The annealing process adopted in the present invention is mainly to ensure that the steel strip obtains uniformly dispersed granular bainite in the shape of a coral sea in the length, width and thickness directions.

[0050] Based on this, firstly, the steel strip is heated to 840-900℃ and kept warm at a heating rate of ≤50℃ / s, in order to ensure that the steel strip obtains the original austenite structure as uniform as possible. Then, it is cooled to 700-780℃ and kept warm at a cooling rate of 2-20℃ / s. On the one hand, it is to form a certain amount of ferrite structure at this time, thereby greatly reducing the possibility of martensite formation in the subsequent low-temperature bainite transformation process. On the other hand, it is to reduce the temperature at the beginning of rapid cooling and reduce the temperature drop in the rapid cooling interval to reduce the influence of heat exchange fluctuations during rapid cooling on the organizational properties; then, through the three annealing process designs of rapid cooling, heating and slow cooling in the bainite phase region, a coral sea-like uniformly dispersed granular bainite can be formed. Among them, in the rapid cooling stage, if the temperature is too low, martensite is easy to form, and if the temperature is too high, upper bainite is easy to form. At the same time, the control of the cooling rate is also critical. Too fast cooling rate is not conducive to the control of the uniformity of the steel strip organization, while too slow cooling rate is easy to form ferrite, pearlite and upper bainite. The reheating stage and the slow cooling stage are designed to allow the steel strip to undergo phase transformation in the granular bainite transformation range over a relatively long period of time, thereby forming a coral sea-like uniformly dispersed granular bainite.

[0051] Furthermore, in the hot rolling step of the manufacturing method of the present invention, the heating temperature is controlled to be 1180-1280°C, and the finishing rolling temperature is 870-970°C.

[0052] In this embodiment, the heating temperature is controlled to be 1180-1280°C, on the one hand to ensure that the slab can be heated to a uniform temperature everywhere, and on the other hand, a higher heating temperature can also ensure that the subsequent finishing rolling temperature is 870-970°C. If the heating temperature is too low, the slab will be heated unevenly and the finishing rolling temperature will be too low. If the heating temperature is too high, the slab surface will be severely oxidized, and finally the slab surface structure will be abnormal after annealing.

[0053] The finishing temperature of finishing rolling is controlled at 870-970℃. On the one hand, it is to avoid the transformation of austenite to ferrite of the steel strip during finishing rolling. On the other hand, a higher finishing temperature is beneficial to the control of the cross-sectional size and shape of the steel strip. If the finishing temperature is too low, ferrite transformation is likely to occur during or after finishing rolling, which is not conducive to the control of the structure during subsequent annealing. If the finishing temperature is too high, more cooling water is required to cool the steel strip during cooling after rolling, and too much cooling water input is not conducive to the uniform control of the hot-rolled structure during coiling.

[0054] Furthermore, in the hot rolling step of the manufacturing method of the present invention, the difference between the center thickness and the thickness within 40 cm from the edge in the width direction of the steel strip section after finish rolling is controlled to be ≤50 μm.

[0055] In this embodiment, the difference between the center thickness and the thickness within 40 cm from the edge in the width direction of the steel strip section after fine rolling is controlled to be ≤50 μm, mainly to cooperate with the subsequent cold rolling step to control the cross-sectional shape and plate shape of the steel strip during the final continuous annealing to be good, so as to reduce the uneven organizational properties of the finished coil caused by the fluctuation of the cross-sectional shape and plate shape of the steel strip during the final continuous annealing.

[0056] Furthermore, in the manufacturing method described in the present invention, during the entire process of hot rolling, post-rolling cooling and coiling, the temperature difference between the non-middle area and the middle area in the width direction of the steel strip is controlled to be ≤30°C, and the temperature fluctuation between the middle area and the non-middle area in the length direction is controlled to be ≤15°C.

[0057] The process in this embodiment is to ensure the uniformity of the structural properties of the steel strip in the width and length directions after it is rolled by controlling the temperature fluctuation.

[0058] Furthermore, in the post-rolling cooling step of the manufacturing method described in the present invention, the multi-stage cooling by alternating fast cooling and slow cooling specifically includes: in the first stage, the steel strip is cooled to 680-760°C at a cooling rate of 100-200°C / s; in the second stage, the steel strip is cooled to 600-670°C at a cooling rate of 5-25°C / s; in the third stage, the steel strip is cooled to 520-590°C at a cooling rate of 50-150°C / s; in the fourth stage, the steel strip is cooled to 490-570°C at a cooling rate of 5-25°C / s.

[0059] The selection of the step point temperatures of the above cooling sections is designed to be within the ferrite transformation range of the steel strip, so that the steel strip can preferentially transform a small amount of ferrite and pearlite at this stage to ensure the uniformity of the microstructure and properties of the hot coil, thereby greatly reducing the possibility of forming martensite during subsequent low-temperature coiling.

[0060] Furthermore, in the cold rolling step of the manufacturing method described in the present invention, the cold rolling reduction rate is controlled to be ≥30%, and the target thickness of the steel strip is controlled so that the difference between the center point thickness and the thickness at any position within 40 cm from the edge in the width direction of the steel strip section is ≤30 μm.

[0061] In this embodiment, the process parameters are set to control the cross-sectional shape and plate shape of the steel strip after cold rolling to be good, so as to reduce the uneven microstructure and performance of the finished coil caused by the fluctuation of the cross-sectional shape and plate shape of the steel strip during the final continuous annealing.

[0062] Furthermore, in the annealing step of the manufacturing method described in the present invention, when heating and heat preservation are performed, when the heating temperature is ≥870°C, the heat preservation time is ≤2min, and when the heating temperature is <860°C, the heat preservation time is >2min.

[0063] Furthermore, in the manufacturing method described in the present invention, during the entire annealing step, the temperature difference between the non-middle area and the middle area in the width direction of the steel strip is controlled to be ≤10°C at the same time, and the temperature fluctuation between the middle area and the non-middle area in the length direction of the steel strip is controlled to be ≤5°C.

[0064] The process in this embodiment is also to ensure the uniformity of the structure and performance of the steel strip in the width and length directions after coiling by controlling the temperature fluctuation.

[0065] Furthermore, in the annealing step of the manufacturing method described in the present invention, the temperature is heated to 840-900°C at a heating rate of ≤50°C / s and kept warm for 1-4 minutes; then cooled to 700-780°C at a cooling rate of 2-20°C / s and kept warm for 10-40 seconds; then cooled to 360-430°C at a cooling rate of 20-50°C and kept warm for 2.5-10 seconds.

[0066] The ultra-high strength steel strip and the manufacturing method thereof of the present invention have the following advantages and beneficial effects:

[0067] Under the premise of ensuring that the chemical element composition and process are relatively simple and controllable, the present invention obtains ultra-high-strength steel with low anisotropy and high uniformity in the same roll through innovations in composition design, organizational regulation and manufacturing methods.

[0068] In some embodiments, the tensile strength is ≥1000MPa, and the yield strength is ≥780MPa; and the low anisotropy satisfies: the difference in yield strength between the transverse and longitudinal directions at the same position on the steel strip is ≤25MPa, and the difference in tensile strength is ≤20MPa; the mechanical uniformity of the same coil satisfies: for the same steel coil, along its length or width direction, the difference in yield strength at different positions in the same tensile direction is ≤25MPa, and the difference in tensile strength is ≤20MPa.

[0069] In some embodiments, the ultra-high strength steel strip of the present invention not only has the above-mentioned properties, but also has good formability, with a breaking elongation of ≥10% and a hole expansion rate of ≥50%.

[0070] The ultra-high strength steel strip described in the present invention can be used for automotive parts with strict requirements on part size accuracy and service stability, such as front seat slide rails in the car cockpit system and other automotive structural parts. It represents a new design concept of "high, precise and advanced" refined, stabilized and differentiated products and has good promotion prospects and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 This is a microstructure photograph of the ultra-high strength steel strip of Example 1 magnified 3000 times. DETAILED DESCRIPTION

[0072] The ultra-high strength steel strip and the method for manufacturing the same according to the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an undue limitation on the technical solution of the present invention.

[0073] Examples 1-7 and Comparative Examples 1-2

[0074] The ultra-high strength steel strips of Examples 1-7 and the comparative steel strips of Comparative Examples 1-2 of the present invention are prepared by the following steps:

[0075] (1) Smelting and casting are carried out according to the chemical composition ratio designed in Table 1.

[0076] (2) Hot rolling: control the heating temperature to 1180-1280°C and the finishing temperature to 870-970°C.

[0077] In some embodiments, it is preferred to control the difference between the center thickness and the thickness within 40 cm from the edge in the width direction of the steel strip section after finish rolling to be ≤50 μm.

[0078] (3) Post-rolling cooling and coiling: Post-rolling cooling adopts a multi-stage cooling method of alternating fast cooling and slow cooling. Finally, for the area outside 100m of the head and tail of the steel strip, the main body of the steel strip is cooled to the main coiling temperature of 440℃~520℃ at a cooling rate of 5~100℃ for coiling. For the area within 100m of the head and tail of the steel strip, the head and tail of the steel strip are cooled to the head and tail coiling temperature of 480℃~560℃ at a cooling rate of 5~25℃ for coiling.

[0079] In some embodiments, the above-mentioned multi-stage cooling by alternating fast cooling and slow cooling may specifically include: cooling the steel strip to 680-760°C at a cooling rate of 100-200°C / s in the first stage; cooling the steel strip to 600-670°C at a cooling rate of 5-25°C / s in the second stage; cooling the steel strip to 520-590°C at a cooling rate of 50-150°C / s in the third stage; cooling the steel strip to 490-570°C at a cooling rate of 5-25°C / s in the fourth stage, and making the steel strip temperature at the end of the fourth stage lower than the steel strip temperature at the end of the third stage. The subsequent cooling of the steel strip to the coiling temperature is the fifth stage cooling, and making the coiling temperature at each location of the steel strip lower than the steel strip temperature at the corresponding position at the end of the fourth stage.

[0080] (4) Pickling and cold rolling: Control the cold rolling reduction rate ≥ 30%.

[0081] In some embodiments, the target thickness of the steel strip is controlled so that the difference between the thickness at the center point and the thickness at any position within 40 cm from the edge in the width direction of the steel strip section is ≤30 μm.

[0082] In some preferred embodiments, during the entire process of hot rolling, post-rolling cooling and coiling, the temperature difference between the non-middle area and the middle area in the width direction of the steel strip is controlled to be ≤30°C, and the temperature fluctuation between the middle area and the non-middle area in the length direction is controlled to be ≤15°C.

[0083] In some more specific embodiments, during the whole process of hot rolling, cooling after rolling and coiling, 7 points of equal spacing temperature measurement and temperature control can be adopted in the width direction of the steel strip. All temperatures in the hot rolling, cooling after rolling and coiling steps are the temperatures of the middlemost area of ​​the 7-point equal spacing temperature measurement and temperature control, and the temperature difference between the other 6 areas and the middle area in the width direction can be controlled to be ≤30°C. All temperatures in the hot rolling, cooling after rolling and coiling steps refer to the average temperature of the middlemost area of ​​the steel strip within the required length range, and the temperature fluctuation within the length range is ≤15°C. When the length range is not specifically stated, it refers to the full length range of the steel strip.

[0084] (5) Annealing: heat to 840-900°C at a heating rate of ≤50°C / s and keep warm for 1-4 min; then cool to 700-780°C at a cooling rate of 2-20°C / s and keep warm for 10-40 s; then cool to 360-430°C at a cooling rate of 20-50°C and keep warm for 2.5-10 s; then heat to 440-480°C at a heating rate of 5-30°C / s; then cool to 330-400°C at a cooling rate of 0.1-0.5°C / s; finally cool to room temperature at a cooling rate of 15-50°C / s to form a coil.

[0085] Among them, when the heating temperature is ≥870°C, the holding time is ≤2min, and when the heating temperature is <870°C, the holding time is >2min.

[0086] In some embodiments, during the entire annealing step, the temperature difference between the non-middle area and the middle area in the width direction of the steel strip is controlled to be ≤10°C at the same time, and the temperature fluctuation between the middle area and the non-middle area in the length direction of the steel strip is controlled to be ≤5°C.

[0087] In some more specific embodiments, during the entire annealing step, 7 points of evenly spaced temperature measurement and temperature control can be used in the width direction of the steel strip. All temperatures in the annealing step are the temperatures of the middlemost area of ​​the 7-point evenly spaced temperature measurement and temperature control, and the temperature difference between the other 6 areas in the width direction and the middle area can be controlled to be ≤10°C. All temperatures in the annealing step refer to the average temperature of the middlemost area of ​​the steel strip within the required length range, and the temperature fluctuation within the length range is ≤5°C. When the length range is not specifically stated, it refers to the full length of the steel strip.

[0088] It should be noted that the chemical composition design and related manufacturing processes used in the ultra-high strength steel strips of Examples 1-7 all meet the specification requirements of the present invention. Correspondingly, the chemical composition design and related manufacturing processes used in the comparative steel strips of Comparative Examples 1-2 all have process parameters that do not meet the design requirements of the present invention.

[0089] Table 1 lists the mass percentages of the chemical elements of the ultra-high strength steel strips of Examples 1-7 and the comparative steel strips of Comparative Examples 1-2.

[0090] Table 1. (wt%, the balance is Fe and other inevitable impurities except P, S, N)

[0091] serial number C Si Mn B Al Cr Mo P S N Ti Nb V (Cr+Mo) / C Example 1 0.16 0.35 1.7 0.0025 0.02 0.3 0.2 0.008 0.002 0.004 0.001 0.002 0.004 3.13 Example 2 0.14 0.5 2.0 0.004 0.04 0.2 0.25 0.012 0.003 0.0038 0.002 0.001 0.006 3.21 Example 3 0.15 0.4 1.8 0.003 0.025 0.35 0.1 0.011 0.001 0.0035 0.004 0.003 0.003 3.00 Example 4 0.19 0.15 1.4 0.001 0.01 0.4 0.15 0.006 0.004 0.0025 0.003 0.004 0.001 2.89 Example 5 0.20 0.25 1.6 0.002 0.03 0.25 0.35 0.009 0.001 0.0035 0.001 0.002 0.005 3.00 Example 6 0.13 0.45 1.9 0.0035 0.035 0.1 0.3 0.01 0.001 0.0015 0.006 0.005 0.003 3.08 Example 7 0.18 0.2 1.5 0.0015 0.015 0.15 0.4 0.005 0.001 0.0018 0.005 0.006 0.002 3.06 Comparative Example 1 0.21 0.25 1.6 0.0015 0.02 0.15 0.15 0.008 0.002 0.004 0.001 0.002 0.001 1.43 Comparative Example 2 0.15 0.4 1.8 0.003 0.025 0.35 0.1 0.011 0.001 0.0035 0.004 0.003 0.003 3.00

[0092] Table 2-1, Table 2-2, Table 2-3 and Table 2-4 list the specific process parameters of the ultra-high strength steel strips of Examples 1-7 and the comparative steel strips of Comparative Examples 1-4 in the above process steps.

[0093] Table 2-1.

[0094]

[0095] Table 2-2.

[0096]

[0097] Table 2-3

[0098]

[0099] Table 2-4

[0100]

[0101] The ultra-high strength steel strips of Examples 1-7 were sampled respectively, and their microstructures were observed and tested. The microstructure observation results are listed in Table 3 below.

[0102] Table 3.

[0103]

[0104] In addition, based on the observation of each embodiment, the area of ​​granular bainite in the ultra-high strength steel strip of all embodiments is ≤5 μm 2 , aspect ratio ≤2:1.

[0105] For all ultra-high strength steel strips of Examples 1 to 7, any cross-sectional area within the entire region 30 μm from the upper and lower surfaces of the steel strip in the thickness direction is ≤50 μm. 2 The granular bainite is distributed in the region of 0.1 μm.

[0106] For all ultra-high strength steel strips of Examples 1 to 7, any cross-sectional area within the entire region 20 μm from the upper and lower surfaces of the steel strip in the thickness direction is ≤10 2 The granular bainite is distributed in the region of 0.1 μm.

[0107] also, Figure 1 The microstructure of the ultra-high strength steel strip of Example 1 is also shown at 3000 times magnification. Figure 1 It can be seen that the ultra-high strength steel strip has uniformly dispersed granular bainite in a coral sea shape.

[0108] In addition, the obtained ultra-high strength steel strips of Examples 1-7 and the comparative steel strips of Comparative Examples 1-2 were sampled and tested for mechanical properties to evaluate their anisotropy and same-roll uniformity, and the anisotropy and same-roll uniformity of each embodiment and comparative example are listed in Tables 4-1 to 4-9. The relevant mechanical property testing methods are as follows:

[0109] Tensile performance test: GB / T228.1-2021 "Tensile test of metal materials Part 1: Room temperature test method" is used.

[0110] The hole expansion rate of steel is determined by the hole expansion test. The central hole of the specimen is expanded by pressing the specimen with a hole in the center into the die using a punch until necking or through cracks appear at the edge of the plate hole. Since the preparation method of the original hole in the center of the specimen and the corresponding quality of the edge of the original hole have a great influence on the hole expansion rate test results, the test and test method are carried out according to the hole expansion rate test method specified in the ISO / DIS 16630 standard, and the central original hole is in the form of a punched hole (corresponding to the processing method with the worst quality of the edge of the original hole).

[0111] Table 4-1. Example 1

[0112]

[0113] Table 4-2. Example 2

[0114]

[0115]

[0116] Table 4-3. Example 3

[0117]

[0118] Table 4-4. Example 4

[0119]

[0120]

[0121] Table 4-5. Example 5

[0122]

[0123] Table 4-6. Example 6

[0124]

[0125]

[0126] Table 4-7. Example 7

[0127]

[0128] Table 4-8. Comparative Example 1

[0129]

[0130]

[0131] Table 4-9. Comparative Example 2

[0132]

[0133] Note: The "strength difference" in Table 4-1 to Table 4-9 refers to the maximum and minimum differences of all test points in the longitudinal or transverse stretching direction of the full length and full width of the steel strip.

[0134] It can be seen from the above Tables 4-1 to 4-9 that all embodiments of the present invention meet the requirements of tensile strength ≥ 1000MPa, yield strength ≥ 780MPa, elongation at break ≥ 10%, and hole expansion rate ≥ 50%; at the same time, the anisotropy meets the requirements: the difference in yield strength between the transverse and longitudinal directions at the same position on the steel strip is ≤ 25MPa, and the difference in tensile strength is ≤ 20MPa; the mechanical uniformity of the same coil meets the requirements: for the same steel coil, along its length or width direction, the difference in yield strength at different positions in the same tensile direction is ≤ 25MPa, and the difference in tensile strength is ≤ 20MPa.

[0135] In Comparative Example 1, not only the C content exceeds the upper limit of the design requirements, but also fails to meet 2.7≤(Cr+Mo) / C≤3.3, (Cr+Mo) / C is only 1.43. At this time, the component has extremely high requirements on the cooling rate. In the actual manufacturing process, the cooling rate in the annealing rapid cooling section does not meet the requirements, which ultimately leads to abnormal product performance. Not only the yield strength and tensile strength are too low, the hole expansion rate is insufficient, but also the anisotropy is high and the uniformity of the same roll is low.

[0136] Although the component design of Comparative Example 2 meets the requirements of the present invention, the cooling rate in the manufacturing process is too high and does not meet the requirements of the present invention. Although the mechanical properties of the product meet the requirements, the uniformity of the same roll is poor and the strength difference between different positions is too large.

[0137] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0138] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.

Claims

1. An ultra-high strength steel strip containing Fe and inevitable impurity elements, characterized in that: It also contains the following chemical elements in the following mass percentages: C: 0.13~0.20%; Si: 0.15~0.50%; Mn: 1.4~1.9%; B:0.001~0.004%; Al: 0.01~0.04%; Cr: 0.1~0.4%; Mo: 0.1~0.4%; Ti+V+Nb≤0.02%; Its microstructure consists of uniformly dispersed granular bainite in the shape of a coral sea.

2. The ultra-high strength steel strip according to claim 1, characterized in that: The mass percentage of each chemical element is: C: 0.13~0.20%; Si: 0.15~0.50%; Mn: 1.4~2.0%; B: 0.001~0.004%; Al: 0.01~0.04%; Cr: 0.1~0.4%; Mo: 0.1~0.4%; Ti+V+Nb≤0.02%; the balance is Fe and unavoidable impurity elements.

3. The ultra-high strength steel strip according to claim 1 or 2, characterized in that: The mass percentage of each chemical element satisfies at least one of the following: C:0.14~0.18%; Ti+V+Nb≤0.02%.

4. The ultra-high strength steel strip according to claim 1 or 2, characterized in that: The mass percentage of each chemical element also satisfies: 2.7≤(Cr+Mo) / C≤3.

3.

5. The ultra-high strength steel strip according to claim 1 or 2, characterized in that: The mass percentage of the inevitable impurity elements satisfies at least one of the following conditions: P≤0.012%, S≤0.003%, N≤0.004%.

6. The ultra-high strength steel strip according to claim 1 or 2, characterized in that: The volume phase ratio of the granular bainite is ≥95%.

7. The ultra-high strength steel strip according to claim 1, characterized in that: The area of ​​the granular bainite is ≤5 μm 2 , aspect ratio ≤2:

1.

8. The ultra-high strength steel strip according to claim 1, characterized in that: Any cross-sectional area within the entire area 30μm from the upper and lower surfaces of the steel strip in the thickness direction is ≤50 2 The granular bainite is distributed in the region of 0.1 μm.

9. The ultra-high strength steel strip according to claim 1, characterized in that: Any cross-sectional area within the entire area 20μm from the upper and lower surfaces of the steel strip in the thickness direction is ≤10 2 The granular bainite is distributed in the region of 0.1 μm.

10. The ultra-high strength steel strip according to claim 6, characterized in that: The microstructure also includes ferrite, and the volume phase ratio of the ferrite is 0.1-4.5%.

11. The ultra-high strength steel strip according to claim 1 or 2, characterized in that: Its tensile strength is ≥1000MPa, and its yield strength is ≥780MPa; and its low anisotropy satisfies: the difference in yield strength between the transverse and longitudinal directions at the same position on the steel strip is ≤25MPa, and the difference in tensile strength is ≤20MPa; the mechanical uniformity of the same coil satisfies: for the same steel coil, the difference in yield strength between different positions in the same tensile direction along its length or width is ≤25MPa, and the difference in tensile strength is ≤20MPa.

12. The ultra-high strength steel strip according to claim 11, characterized in that: Its elongation at break is ≥10%, and / or its hole expansion rate is ≥50%.

13. The method for manufacturing an ultra-high strength steel strip according to any one of claims 1 to 12, characterized in that: Includes steps: smelting and casting; Hot rolling; Post-rolling cooling and coiling: Post-rolling cooling adopts fast cooling and slow cooling alternately for multi-stage cooling. Finally, for the area outside 100m of the head and tail of the steel strip, the main body of the steel strip is cooled to the main coiling temperature of 440℃~520℃ at a cooling rate of 5~100℃ for coiling. For the area within 100m of the head and tail of the steel strip, the head and tail of the steel strip are cooled to the head and tail coiling temperature of 480℃~560℃ at a cooling rate of 5~25℃ for coiling. Pickling and cold rolling; Annealing: heat to 840-900°C at a heating rate of ≤50°C / s and keep warm; then cool to 700-780°C at a cooling rate of 2-20°C / s and keep warm; then cool to 360-430°C at a cooling rate of 20-50°C and keep warm; then heat to 440-480°C at a heating rate of 5-30°C / s; then cool to 330-400°C at a cooling rate of 0.1-0.5°C / s; finally cool to room temperature at a cooling rate of 15-50°C / s and coil.

14. The manufacturing method according to claim 13, characterized in that: In the hot rolling step, the heating temperature is controlled to be 1180-1280°C, and the finishing rolling temperature is controlled to be 870-970°C.

15. The manufacturing method according to claim 13, characterized in that: In the hot rolling step, the difference between the center thickness and the thickness within 40 cm from the edge in the width direction of the steel strip section after finish rolling is controlled to be ≤50 μm.

16. The manufacturing method according to claim 13, characterized in that: During the entire process of hot rolling, post-rolling cooling and coiling, the temperature difference between the non-middle area and the middle area in the width direction of the steel strip is controlled to be ≤30°C at the same time, and the temperature fluctuation between the middle area and the non-middle area in the length direction is controlled to be ≤15°C.

17. The manufacturing method according to claim 13, characterized in that: In the post-rolling cooling step, the multi-stage cooling by alternating fast cooling and slow cooling specifically includes: in the first stage, the steel strip is cooled to 680-760°C at a cooling rate of 100-200°C / s; in the second stage, the steel strip is cooled to 600-670°C at a cooling rate of 5-25°C / s; in the third stage, the steel strip is cooled to 520-590°C at a cooling rate of 50-150°C / s; in the fourth stage, the steel strip is cooled to 490-570°C at a cooling rate of 5-25°C / s.

18. The manufacturing method according to claim 13, characterized in that: In the cold rolling step, the cold rolling reduction rate is controlled to be ≥30%, and the target thickness of the steel strip is controlled so that the difference between the center point thickness and the thickness at any position within 40 cm from the edge in the width direction of the steel strip section is ≤30μm.

19. The manufacturing method according to claim 13, characterized in that: In the annealing step, when heating and holding are performed, when the heating temperature is ≥870°C, the holding time is ≤2 min, and when the heating temperature is <870°C, the holding time is >2 min.

20. The manufacturing method according to claim 13, characterized in that: During the entire annealing step, the temperature difference between the non-middle area and the middle area in the width direction of the steel strip is controlled to be ≤10°C at the same time, and the temperature fluctuation between the middle area and the non-middle area in the length direction of the steel strip is controlled to be ≤5°C.

21. The manufacturing method according to claim 13, characterized in that: In the annealing step, the material is heated to 840-900°C at a heating rate of ≤50°C / s and kept at this temperature for 1-4 minutes; then cooled to 700-780°C at a cooling rate of 2-20°C / s and kept at this temperature for 10-40 seconds; then cooled to 360-430°C at a cooling rate of 20-50°C and kept at this temperature for 2.5-10 seconds.

Citation Information

Patent Citations

  • Kipah-level bainite steel with ultrahigh yield ratio and manufacturing method of Kipah-level bainite steel

    CN114107785A

  • Ultra-high strength strip steel and its production process

    CN1888117A